Projeto Orquestra Sinfônica Jovens de Sergipe: arte e história - Santos, Vera Núbia (2009)
The reflection in this work aims to remember the Youth s Symphonic Orchestra Project from Sergipe, developed in 2005 and 2006 in the cities from Aracaju and Itabaiana, as a privileged activity of an art expression, shown as a form of social inclusion for children and young people. It used as a theoretical-methodological orientation Georg Lukács and Ernst Fisher s reflections in the sense of the appropriation of the art as a reality reflection and a need of the social being. This indication s objective was to understand the art as a mediation possibility in the Social Work, with a special attention to the development of a project that, maintained by the State s support, can only be continued with the help of a civil society entity. The relation between the State and the Society represents, in this sense, one of the central elements to understand the appearing and the decadence of this project. The documental research, the use of printed report and the project s coordinator and conductor s interview could make this thesis possible. The subtleties, that were not always in evidence while the project was being developed, were scrutinized and the mediation possibility between involved people and the social reality was elucidated